THE LEGITIMATION CRISIS OF THE POLITICAL AND THE INVESTITURE OF TECHNOCRACY AS CONSIDERED THROUGH THE PERSPECTIVE OF GIORGIO AGAMBEN’S THEORY - Ciprian Răzvan LICĂ (Studia Universitatis Babeș-Bolyai. Philosophia)
The Legitimation Crisis of the Political and the Investiture of Technocracy as Considered through the Perspective of Giorgio Agamben’s Theory. Under the conditions of the society of the spectacle, delivered entirely to consumerism as its end, the link between sovereignty and government that traditionally legitimized political power is dissolving in what appears to be a managerial paradigm of power. Simultaneously with this, trust in the given word, as well as in the authenticity of any form of inter-human communication in general, including political speech, is receding. How does this emergent paradigm legitimize itself?